The Analysis of learning interest in three-dimensional material (Utilizing Augmented Reality Features in Geogebra 3D) - Rukmana, Indra; Rosmayanti, Imalia Dwi; Nurizza, Shendy Septyaneu; Apriani, Meta; Latifah, Afiatul; Scarayu, Hana Mutiara; Masta, Al Azhary; Ulfa, Nadia; Taqiyuddin, Muhammad (Universitas Sarjanawiyata Tamansiswa, 2025)
This research is motivated by the results of observations which show that the results of the three-dimensional daily assessments and end-of-semester assessments are still not optimal. This is influenced by several factors, especially the student's interest in learning in class. They still have difficulty visualizing the three dimensions so in calculating the questions given, they still experience difficulties completing them. Three-dimensional material requires a good understanding of the shapes of three-dimensional space and related concepts. Therefore, the Augmented Reality (AR) feature is needed in the Geogebra application. This research aims to analyze students' learning interests by using the Augmented Reality (AR) feature in the Geogebra application. This research used a qualitative approach where the research subjects were 61 students consisting of 33 students in class XII IPA 1 and 28 students in class XII IPS 1 at SMAIT Raudhatul Jannah Cilegon. The research results show that the presentation of each indicator on the student interest scale questionnaire has an average of 80.19%, which means that almost all students already have an interest in learning three-dimensional material using the Augmented Reality (AR) feature in the Geogebra application. It is hoped that other researchers can develop the results of this research, as well as improve the quality of learning, especially in mathematics learning with the help of the Geogebra application to increase insight.